Sequence Analysis and FISH Mapping of Four Satellite DNA Families among Cervidae - Vozdova, Miluse; Kubickova, Svatava; Cernohorska, Halina; Fröhlich, Jan; Martínková, Natália; Rubes, Jiri (Genes, 2020)
Centromeric and pericentromeric chromosome regions are occupied by satellite DNA. Satellite DNAs play essential roles in chromosome segregation, and, thanks to their extensive sequence variability, to some extent, they can also be used as phylogenetic markers. In this paper, we isolated and sequenced satellite DNA I-IV in 11 species of Cervidae. The obtained satellite DNA sequences and their chromosomal distribution were compared among the analysed representatives of cervid subfamilies Cervinae and Capreolinae. Only satI and satII sequences are probably present in all analysed species with high abundance. On the other hand, fluorescence in situ hybridisation (FISH) with satIII and satIV probes showed signals only in a part of the analysed species, indicating interspecies copy number variations. Several indices, including FISH patterns, the high guanine and cytosine (GC) content, and the presence of centromere protein B (CENP-B) binding motif, suggest that the satII DNA may represent the most important satellite DNA family that might be involved in the centromeric function in Cervidae. The absence or low intensity of satellite DNA FISH signals on biarmed chromosomes probably reflects the evolutionary reduction of heterochromatin following the formation of chromosome fusions. The phylogenetic trees constructed on the basis of the satellite I-IV DNA relationships generally support the present cervid taxonomy.
Keywords: cervid phylogeny; DNA Copy Number Variations; centromera; hybridizace in situ fluorescenční; Centromere; Repetitive Sequences, Nucleic Acid; heterochromatin; centromere; variabilita počtu kopií segmentů DNA; FISH; satelitní DNA; Animals; lidé; Ruminants; sequencing; Heterochromatin; Humans; DNA, Satellite; zvířata; repetitivní sekvence nukleových kyselin; In Situ Hybridization, Fluorescence; satellite DNA; přežvýkavci